Gender differences in cardiovascular disease risk factors, treatments and complications in patients with type 2 diabetes: the RIACE Italian multicentre study. (22nd April 2013) - Penno, G.; Solini, A.; Bonora, E.; Fondelli, C.; Orsi, E.; Zerbini, G.; Trevisan, R.; Vedovato, M.; Gruden, G.; Laviola, L.; Nicolucci, A.; Pugliese, G.; et al.
Abstract Objectives Poorer control of risk factors for cardiovascular disease (CVD) has been reported in diabetic women, as compared with diabetic men. It has been proposed that this finding is due to gender disparities in treatment intensity. We investigated this hypothesis in a large contemporary cohort of subjects with type 2 diabetes. Design Observational, cross‐sectional study. Subjects and setting Consecutive patients with type 2 diabetes from the Renal Insufficiency And Cardiovascular Events (RIACE) Italian multicentre study (n = 15 773), attending 19 hospital‐based diabetes clinics in 2007–2008. Main outcome measures Traditional CVD risk factors, macro‐ and microvascular complications and current glucose‐, lipid‐ and blood pressure (BP)‐lowering treatments were assessed. Results Although CVD was more prevalent in men, women showed a less favourable CVD risk profile and worse performance in achieving treatment targets for haemoglobin A1c, LDL, HDL and non‐HDL cholesterol, systolic blood pressure (BP) and in particular obesity [body mass index (BMI) and waist circumference], but not for triglycerides and diastolic BP. However, women were more frequently receiving pharmacological treatment for hypertension and to a lesser extent hyperglycaemia and dyslipidaemia than men, and female gender remained an independent predictor of unmet therapeutic targets after adjustment for confounders such as treatments, BMI, duration of diabetes and, except for the systolic BP goal, age. Conclusions In women with type 2 diabetes from the RIACE cohort, a more adverse CVD risk profile and a higher likelihood of failing treatment targets, compared with men, were not associated with treatment differences. This suggests that factors other than gender disparities in treatment intensity are responsible.